2006
DOI: 10.1021/ja062863j
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Luminescence Patterning Based on Multiscaled Self-Assembly

Abstract: This communication describes a procedure for fabrication of hierarchical luminescence patterns based on the template-assisted assembly of CdSe nanocrystals on a self-assembled structure with green-emitting microstripes, as well as the photoinduced fluorescence enhancement of CdSe nanocrystals and photobleaching of dyes. The technique is low-cost and high-throughput and can be extended to many material combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…A detailed description of the pattern formation and some of the applications is given in the literature [16,17]. Previous studies have shown that DPPC stripe patterns can be utilized as a template to pattern nanocrystals [18][19][20] or proteins [21]. Recently, the DPPC stripe pattern was introduced as a template for patterning luminescent organic molecules like 3(5)-(9-anthryl) pyrazole (ANP) [22], perylene [23] and sexiphenyl (6P), whose chemical structures are given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the pattern formation and some of the applications is given in the literature [16,17]. Previous studies have shown that DPPC stripe patterns can be utilized as a template to pattern nanocrystals [18][19][20] or proteins [21]. Recently, the DPPC stripe pattern was introduced as a template for patterning luminescent organic molecules like 3(5)-(9-anthryl) pyrazole (ANP) [22], perylene [23] and sexiphenyl (6P), whose chemical structures are given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchically ordered structures have attracted a great deal of attention because they hold promise for numerous applications such as photonic devices, [1,2] micro-structured electrode surfaces, [3] biosensor arrays, [4] membranes for separation, catalysts, [5] and lithographic masks for complex structures. [6] The multilevel ordering of a hierarchical structure facilitates incorporation of diverse functions simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Various bottom-up fabrication methods utilizing self-assembling materials have been combined with top-down fabrication approaches to yield hierarchically ordered structures. [1,2,[18][19][20][21][22][23][24][25] In these approaches, a length scale in the finally prepared structure is practically determined by the choice of self-assembling material, thus prohibiting dynamic control over characteristic length scales. Moreover, complex chemistry including highly toxic agents is frequently involved in the fabrication process, which limits application towards diverse polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method for the nanofabrication hierarchical luminescence patterning is proposed by Chen et al [166] . Instead of e -beam lithography (EBL) and photolithography, this method offers a self -assembly solution to the nanofabrication.…”
Section: Hierarchical Luminescence Patterning By Multiscaled Self -Asmentioning
confidence: 99%